Development of a model for determining the optimum composition of RDF-fuel in the Republic of Belarus - Sanin, Heorhi K.; Misiuchenka, Viktoryia M.; Morozov, Egor A. (Journal of the Belarusian State University. Ecology, 2022)
The article presents and substantiates a model for determining the blend composition of RDF fuel from municipal waste. The main goal of developing the model presented in the article was to prove the impossibility and inadmissibility of burning plastics of unknown composition as fuel in cement kilns as potential sources of formation of large volumes of persistent organic pollutants. This is the best justification for the environmental safety of the use of RDF fuel in the Republic of Belarus. With the introduction of a large number of plastics, it is necessary to equip additional emission treatment systems. The article describes the developed methodology for choosing the optimal composition of RDF fuel components, as well as calculating the volume of the gas-air mixture. The mathematical model was developed using the MS Excel program. Its main functions are: entering data into the database, calculating the optimal combinations of the RDF fuel composition, determining the calorific value, moisture content and ash content of the required mixture variant. In addition, the mathematical model analyzes the chemical composition of the required combination and derives indicators of the content of contaminants in the RDF fuel. Such characteristics of RDF fuel as calorific value, humidity, ash content are selected and analyzed. The assessment was made without taking into account emissions of heavy metals such as antimony, arsenic, lead, chromium, cobalt, copper, manganese, nickel, vanadium, cadmium, thallium. Due to the hazardous content of elements in the RDF fuel components, it must strictly not exceed the following values: S - 0.5%, Cl - 0.5%, F - 0.002%, Hg - 0.001%. 210 variants of the component composition of the RDF fuel were analyzed. Using calculations to determine the limits on the content of sulfur oxide, mercury and halogens in emissions, the optimal options for the composition of RDF fuel were determined, of which 12 were found to be satisfactory. The analysis of the content in RDF fuel of elements leading to the formation of certain pollutants (S, Cl, F, Hg), which are persistent organic pollutants, was carried out and their permissible concentrations in emissions during the combustion of RDF fuel were determined. Thus, options for optimal RDF fuel compositions that meet consumer and environmental requirements have been determined.